Study on Ring-Opening Copolymerization of Trioxymethylene and Second Monomer Initiated by Phosphotungstic Acid - Yanhong Li; Yushun Jin; Hongjuan Li; Xiang Li; Yatao Wang; Ruofan Liu; Yibo Wu (Advances in Polymer Technology)
In this study, a series of polyoxymethylene copolymers are synthesized by bulk cationic ring-opening polymerization by 1,3,5-trioxane (TOX) with 1,3-dioxolane (DOX), octamethylcyclotetrasiloxane (D4), and cyclohexane oxide (CHO) as the second monomer using phosphotungstic acid (PTA) as an initiator. The polymer products were characterized by hydrogen nuclear magnetic resonance (1H-NMR), infrared spectroscopy (IR), thermogravimetry (TG), and differential scanning calorimetry (DSC). And the copolymerization energy barrier was calculated at the b3lyp/6-31g(d) calculation level using density functional theory (DFT) to explore the copolymerization ability of the second monomer with 1,3,5-trioxane. The results showed that CHO as the second monomer more easily participated in the copolymerization reaction, and the copolymers showed better thermal stability.